Confronting the complexity of CNT materials1. Issue 24 (28th June 2015) - Vargas-Lara, Fernando; Douglas, Jack F.
<x xml:space="preserve">Abstract</x> The morphology of commercial carbon nanotube (CNT) materials is normally quite complex and we combine molecular dynamics and path-integral computational methods, along with effective medium theory, to model the conductive properties of CNT composites based on a more realistic description of this class of materials. Image shows a simulated "gel" composed of interpenetrating CNT domains.